2022
DOI: 10.2174/1381612828666220722124826
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Promising Agents against COVID-19: Secondary Metabolites and Mechanistic Aspects

Abstract: Background: Coronavirus disease 2019 (COVID‑19) is caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) and is associated with a high level of mortality. Objective: This updated review aims to present the most important traditional medicinal plants and some of their secondary metabolites that have previously and more recently been shown to affect viruses and may represent a beneficial contributory step against SARS-CoV-2 as the cause of COVID-19. Moreover, the mechanism aspects of these sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 108 publications
0
5
0
Order By: Relevance
“…Natural products, may be selective antiviral agents [32], but their effectiveness can be limited by high cytotoxicity or low antiviral activity [33]. Further research on the anti-viral properties of phytochemicals will allow for the development of target-specific drug delivery systems.…”
Section: Phytochemicals As Antiviralsmentioning
confidence: 99%
“…Natural products, may be selective antiviral agents [32], but their effectiveness can be limited by high cytotoxicity or low antiviral activity [33]. Further research on the anti-viral properties of phytochemicals will allow for the development of target-specific drug delivery systems.…”
Section: Phytochemicals As Antiviralsmentioning
confidence: 99%
“…In silico analysis has revealed that PSMs could be one of the most valuable drug targets against SARS-CoV-2 [ 37 ]. There are many recent review papers published on the PSMs against SARS-CoV-2 [ 36 , 37 , 125 , 129 , 131 , 132 , 133 , 134 , 135 , 136 ]. A comprehensive list of medicinal plants and their active compounds with inhibitory activity against SARS-CoV-2 can be seen in the recent reviews [ 37 , 131 , 132 , 137 ].…”
Section: Medicinal Plant-produced Metabolites (Small Molecules) Again...mentioning
confidence: 99%
“…Many of them predominantly centre on molecular docking studies, focusing on the theoretical interactions between plant‐derived compounds and the virus at a molecular level (Jamshidnia et al, 2022; Malekmohammad & Rafieian‐Kopaei, 2021). While this offers valuable insights into potential mechanisms of action, it might not fully capture the clinical implications or real‐world therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Aspects of this field have previously been reviewed (Ahmad et al, 2021; Hu et al, 2021; Jamshidnia et al, 2022; Malekmohammad & Rafieian‐Kopaei, 2021; Raimi et al, 2022), and this current review seeks to provide a comprehensive update on the use of phytochemicals and traditional plant‐based remedies as potential new leads for drug development targeting SAR‐CoV‐2. Beyond presenting an inventory of plants and potential benefits, it delves into the intricacies and challenges accompanying these treatments, such as bioavailability issues and potential herb–drug interactions.…”
Section: Introductionmentioning
confidence: 99%